Information Warfare and Digitalization of Politics in a Globalized World - Upadhyay, Prakash (Journal of Political Science, 2023)
Online media of digital methodology has transformed human behaviors from sociocultural and political backing, interest, and participation to sharing supposition or resistance and has transfigured the approach of interaction and thinking—a serious issue for digital anthropology that centeres on internet-related changes of social marvels, a configuration of chaotic pluralism. With the prime argument that digital social media platforms implant feebleness, insecurity, and instability into social and political life, this paper investigates the risks that online media impose on democracy. Based on auxiliary secondary data, the methodology incorporates qualitative verifiable, and analytical methods. The paper's findings contend that the politico-techno-driven political economy of digital innovation has chopped social and democratic institutions and has destabilized worldwide social relations and politics, democracy has been fumed, stormed, and hacked. Social media has created a modern world order of amazing befuddling filter bubble impact where cyber-violence is misogynistic–social media is just like a redirection of Chinese whispers. Subsequently, with, private on-screen characters, governments' data dispersal, and so-called security and safeguarding of citizens' democratic rights, allegorically, George Orwell’s nightmare of 'Animal Farm' unfurling. In a bourgeois populist science of the 'digital panopticon' of technological colonialism, state surveillance, and bourgeois information, humankind is becoming more divided and unsecured and in the future citizens' will be deprived of numerous sociopolitical rights. Future people may fade under the pressure of high-tech colonialism which concurs with the normalization approach that 'offline field' powerful people are powerful 'online' too. Upcoming democracy is probable to be a discreetly 'high-hat' elitist endeavor. Current endeavors and legislations are romanticized as a glass half empty with very few tools to control cyberspace. It is pivotal to invigorate and fortify citizens’ digital agency and self-determination in society, politics, well-being, and economy, otherwise, societies/countries are probable to be more totalitarian.